2017
DOI: 10.1021/acschemneuro.7b00187
|View full text |Cite
|
Sign up to set email alerts
|

Dihydropyrimidine-Thiones and Clioquinol Synergize To Target β-Amyloid Cellular Pathologies through a Metal-Dependent Mechanism

Abstract: The lack of therapies for neurodegenerative diseases arises from our incomplete understanding of their underlying cellular toxicities and the limited number of predictive model systems. It is critical that we develop approaches to identify novel targets and lead compounds. Here, a phenotypic screen of yeast proteinopathy models identified dihydropyrimidine-thiones (DHPM-thiones) that selectively rescued the toxicity caused by β-amyloid (Aβ), the peptide implicated in Alzheimer’s disease. Rescue of Aβ toxicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Despite nearly a billion years of evolutionary divergence, recent estimates showed that a fifth of yeast genes have human disease orthologs lending support to functional discovery investigations using this model [92]. Moreover, thanks to amenability of S. cerevisiae to both classical and advanced molecular genetic techniques, to relatively simple, cheap and quick genetic and environmental manipulations, to the large knowledge base and data collections, high-throughput screening technologies and functional genomics that are not possible in humans [93][94][95], this organism has become a valuable and prevalent eukaryotic model organism to unravel complex and fundamental intracellular mechanisms underlying neurodegeneration [96][97][98][99][100][101][102][103][104].…”
Section: Yeast Models For Admentioning
confidence: 96%
“…Despite nearly a billion years of evolutionary divergence, recent estimates showed that a fifth of yeast genes have human disease orthologs lending support to functional discovery investigations using this model [92]. Moreover, thanks to amenability of S. cerevisiae to both classical and advanced molecular genetic techniques, to relatively simple, cheap and quick genetic and environmental manipulations, to the large knowledge base and data collections, high-throughput screening technologies and functional genomics that are not possible in humans [93][94][95], this organism has become a valuable and prevalent eukaryotic model organism to unravel complex and fundamental intracellular mechanisms underlying neurodegeneration [96][97][98][99][100][101][102][103][104].…”
Section: Yeast Models For Admentioning
confidence: 96%
“…Finally, a yeast-based screen identified clioquinol and dihydropyrimidine-thiones as compounds being able to ameliorate Aβ toxicity in a synergistic, metal-dependent, way via different mechanisms such as increasing Aβ turnover, restoring vesicle trafficking and oxidative stress protection [ 175 , 176 ] ( Table 1 ). Again, also in transgenic mice models, treatment with clioquinol (analogue) compounds inhibited Aβ accumulation [ 177 ] and resulted in a dramatic improvement in learning and memory, accompanied by marked inhibition of AD-like neuropathology [ 178 ].…”
Section: Humanized Yeast Models To Study Aβ Biologymentioning
confidence: 99%
“…As in the previous attempts, the tacrine scaffold was used as template for ChE inhibition while the 3,4-dihydropyrimidin-2(1H)-thione fragment (Figure 7) was selected on the basis of the well known capacity of 3,4dihydropyrimidin-2(1H)-thiones to act not only as good CCB, [36,37] but also as neuroprotective agents toward Abinduced toxicity, likely by attenuating the metal-mediated toxicity of Ab. [38] Twelve racemic tacripyrimidines, differing from substituents at position 3' and 4' of the aromatic ring, were synthesized by a Friedländer-type reaction [33] from 6-amino-4-phenyl-2-thioxo-1,2,3,4-tetrahydropyrimidine-5-carbonitriles [39] and cyclohexanone (see Figure 7). In vitro and in silico studies showed that the biological activity toward the two selected targets was modulated by the substituent attached to the aromatic ring at position C4.…”
Section: Tacripyrimidinesmentioning
confidence: 99%
“…The authors designed these new hybrids to achieve compounds with a more balanced activity towards both ChEs and Ca 2+ channels. As in the previous attempts, the tacrine scaffold was used as template for ChE inhibition while the 3,4‐dihydropyrimidin‐2(1 H )‐thione fragment (Figure ) was selected on the basis of the well known capacity of 3,4‐dihydropyrimidin‐2(1 H )‐thiones to act not only as good CCB,, but also as neuroprotective agents toward A β ‐induced toxicity, likely by attenuating the metal‐mediated toxicity of A β …”
Section: Tacripyrimidinesmentioning
confidence: 99%